복분자가 U937세포의 apoptosis에 미치는 효과 - 이광규(Kwang Kyu Lee); 한종현(Jong Hyun Han); 오찬호(Chan Ho Oh) (동의생리병리학회지, 2009)
Methanol extracts of Rubus Coreanus Miquel (RCM) were found to exhibit apoptosis induction of U937 human histiocytic leukemia cells. Treatment of RCM exerted strong cytotoxicity against U937 human leukemia cells. RCM induced apoptosis of U937 leukemia cells in a dose dependent manner. Nitric oxide (NO) production was increased in RCM-treated RAW264.7 macrophage cell line. RCM increased the p53 and $NFκB$ gene and decreased the $IκB$ gene expression in U937 cells. RCM also increased the $NFκB$ protein expression, but decreased the PCNA and BcL-xL protein expression in cultured U937 cells. These data suggest that RCM are effective on the apoptosis induction of human leukemia cells and anti-cancer properties.